2014
DOI: 10.3390/molecules191221276
|View full text |Cite
|
Sign up to set email alerts
|

Insecticidal Activities of Bark, Leaf and Seed Extracts of Zanthoxylum heitzii against the African Malaria Vector Anopheles gambiae

Abstract: Abstract:The olon tree, Zanthoxylum heitzii (syn. Fagara heitzii) is commonly found in the central-west African forests. In the Republic of Congo (Congo-Brazzaville) its bark is anecdotally reported to provide human protection against fleas. Here we assess the insecticidal activities of Z. heitzii stem bark, seed and leaf extracts against Anopheles gambiae s.s, the main malaria vector in Africa. Extracts were obtained by Accelerated Solvent Extraction OPEN ACCESSMolecules 2014, 19 21277 (ASE) using solvents of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 32 publications
4
21
0
Order By: Relevance
“…1 H NMR spectral data for the pure substances are shown in Table 1 . Spectra of the crude extract have been published previously ([ 16 ], suppl.).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 H NMR spectral data for the pure substances are shown in Table 1 . Spectra of the crude extract have been published previously ([ 16 ], suppl.).…”
Section: Methodsmentioning
confidence: 99%
“…Mosquitoes were reared at 25 ± 5 o C and 80 ± 10 % humidity in the laboratory of IRD, Montpellier. Assay for topical toxicity according to standard WHO protocol [ 17 ] was done as previously described [ 16 ]. Two replicates of 25 non-blood fed 2–5 day-old female mosquitoes (average weight 1.1 mg), were used in each test.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The paracite was then swapped with Giemsa coloured blood. The paracitemia percentage was calculated by comparing the number of infencted erythrocites to 500 erithrocites [13,14]. The formula is as follows: The growth inhibition percentage for each concentration were used in SPSS program to calculate the IC50 in ppm unit.…”
Section: Methodsmentioning
confidence: 99%
“…This is consistent with a previous report that showed mortality rates of mosquitoes declined with increasing polarity of the solvent. These authors showed that water extracts of Zanthoxylum heitzii (Rutaceae) produced the lowest adult mortalities whereas its ethyl acetate and hexane extracts produced higher mortalities against Anopheles gambiae [44]. maxima, the first in the ranges 230-290 nm (band I) and the second in the ranges 400-500 nm (band II).…”
Section: Page 6 Ofmentioning
confidence: 99%